THE ACTIVITY OF MARYAM SULTONMURODOVA (1905-1971) AN UZBEK JADID WOMAN - Tilavova Shahnoza Salohitdinovna (American Journals Publishing, 2024)
In the 20s of the 20th century, a group of talented young people were sent to study in Germany at the initiative of the Jadids in the Turkestan region. Talented girls were among the students sent to study abroad, who aimed to acquire deep, modern knowledge, contribute to the development of their country, and gain a worthy place in society. One of such progressive women is Maryam Sultanmuradova, who has a high potential and is educated. This article provides information about her life, activities, and her role in the Turkestan reform movement.
Keywords: Jaddism, national personnel, abroad, education, press, “Ko‘mak” organization, development, “Guliston”, “Yorqin turmush”, editorial, repression.